2021
DOI: 10.1039/d0cp05363e
|View full text |Cite
|
Sign up to set email alerts
|

Insights from quantum chemical calculations into inner and outer-sphere complexation of plutonium(iv) by monoamide and carbamide extractants

Abstract: The strong influence of the structure of amide derivatives on plutonium extraction properties is rationalized from DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…For the pure DEHBA extractant, the hydrodynamic radius of Ce(IV) is about 13 Å. This value is larger (factor 2.5) than the one estimated to be 7.75 Å by NMR (28,29) and theoretical calculations (25) for Pu(NO 3 ) 4 (DEHBA) 2 in dilute medium ([DEHBA] < 1 mol.L À 1 ). This difference can be explained by the existence of a hydrogen bonding network between the solvates Ce IV (NO 3 ) 4 (DEHBA) n and the DEHBA molecules in the pure solvent, whereas in dilute medium (< 1 mol.L À 1 ) the solvates are isolated.…”
Section: Cyclic Voltammetry Of Ce(iv) In Nn-das Equilibrated With Aqu...mentioning
confidence: 74%
See 1 more Smart Citation
“…For the pure DEHBA extractant, the hydrodynamic radius of Ce(IV) is about 13 Å. This value is larger (factor 2.5) than the one estimated to be 7.75 Å by NMR (28,29) and theoretical calculations (25) for Pu(NO 3 ) 4 (DEHBA) 2 in dilute medium ([DEHBA] < 1 mol.L À 1 ). This difference can be explained by the existence of a hydrogen bonding network between the solvates Ce IV (NO 3 ) 4 (DEHBA) n and the DEHBA molecules in the pure solvent, whereas in dilute medium (< 1 mol.L À 1 ) the solvates are isolated.…”
Section: Cyclic Voltammetry Of Ce(iv) In Nn-das Equilibrated With Aqu...mentioning
confidence: 74%
“…However, few fundamental studies have been reported, and the influence of the structure of N,N-dialkylamides on the extraction properties is not yet fully explained. The structures of Pu(IV) and U(VI) complexes with N,Ndialkyl amides ligands were recently characterized by Guillaumont and coworkers [24,25] using single-crystal Xray diffraction (XRD), extended X-ray absorption fine structure (EXAFS), and theoretical calculations. These studies show that these species are tetra-nitrato complexes solvated by two extractants.…”
Section: Introductionmentioning
confidence: 99%
“…Failali et al . indeed showed that steric hindrance of a monoamide destabilizes the complex Pu(NO 3 ) 4 L 2 when the acyl chain was branched [39] . By rending the inner spheres complexes formation less favorable, this steric hindrance would therefore be responsible of the Pu extraction decrease.…”
Section: Resultsmentioning
confidence: 99%